1991
DOI: 10.1037/0021-9010.76.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Relations of job characteristics from multiple data sources with employee affect, absence, turnover intentions, and health.

Abstract: Much of the evidence in support of job characteristics theory is limited to incumbent reports of job characteristics. In this study, job characteristics data from three independent sources--incumbents, ratings from job descriptions, and the Dictionary of Occupational Titles--were used. Convergent validities of incumbent reports with other sources were quite modest. Although incumbent reports of job characteristics correlated significantly with several employee outcomes (job satisfaction, work frustration, anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
2
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(198 citation statements)
references
References 39 publications
7
185
2
4
Order By: Relevance
“…It is not uncommon to measure intentions to stay and turnover with single-item scales (Lounsbury & Hoopes, 1986;O'Neil & Mone, 1998;Schneider & Bowen, 1985;Spector & Jex, 1991;Thompson & Prottas, 2005). Thus, we measured intentions to stay with the sole item, "It is likely that I will leave the organization in the next 12 months" (reverse-coded).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon to measure intentions to stay and turnover with single-item scales (Lounsbury & Hoopes, 1986;O'Neil & Mone, 1998;Schneider & Bowen, 1985;Spector & Jex, 1991;Thompson & Prottas, 2005). Thus, we measured intentions to stay with the sole item, "It is likely that I will leave the organization in the next 12 months" (reverse-coded).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, information obtained from supervisors as opposed to other channels may have different effects on internals' versus externals' intentions to stay. With respect to the role of job significance, future research would benefit from considering job scope and complexity more broadly by including other evaluation sources of job characteristics beyond self-reports (Spector & Jex, 1991;Wong, Hui, & Law, 1998).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…High turnover intentions among employees has been associated with strenuous work conditions, such as high work load [46], low advancement possibilities [47], low skill variety [48], low social support [49], low autonomy and feedback [50,51]. Several studies [42,43] have shown positive effects of mobility from jobs that do not fit the individual's competence or abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The situation also makes clear that persistence in the publication process matters. Good examples in this regard are Buckley, Jackson, Bolino, Veres, and Feild (2007), Combs, Liu, Hall, and Ketchen (2006), and the aforementioned Spector and Jex (1991). These articles were rejected at three, two, and three journals, respectively, before they were accepted by very fine outlets (i.e., the first two at Personnel Psychology and the third at the Journal of Applied Psychology).…”
Section: Paradigm Schmaradigmmentioning
confidence: 99%
“…Additionally, because the paper most likely becomes improved over time, the chances are even better than the numbers might indicate. An example of that is an article (Spector & Jex, 1991) ultimately published in the Journal of Applied Psychology. This paper was rejected in order from JAP, PP, and the Journal of Occupational and Organizational Psychology.…”
Section: Paradigm Schmaradigmmentioning
confidence: 99%